1993
DOI: 10.1136/gut.34.4.558
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse vascular ectasia of the antrum, duodenum, and jejunum in a patient with nodular regenerative hyperplasia. Lack of response to portosystemic shunt or gastrectomy.

Abstract: The case is reported of a 70 year old man who presented with severe anaemia because of chronic gastrointestinal blood loss. This loss was ascribed to vascular ectasia resembling the gastric antral vascular ectasia syndrome but extended to include the antrum, the duodenum, the jejunum, and, possibly, the cardiac area. This condition was associated with portal hypertension as a result of nodular regenerative hyperplasia. Consecutive treatments including sucralfate, prostaglandin E2, propranolol, organic nitrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
3

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 21 publications
0
24
0
3
Order By: Relevance
“…Procedures aimed at reducing portal pressures include surgical construction of portosystemic shunts (SPSS) and radiological placement of TIPS. Initial case reports showed disappointing results [30, 37]. A small series of 8 (7 TIPS, 1 SPSS) showed a significant reduction in portal pressures in 7 cases.…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures aimed at reducing portal pressures include surgical construction of portosystemic shunts (SPSS) and radiological placement of TIPS. Initial case reports showed disappointing results [30, 37]. A small series of 8 (7 TIPS, 1 SPSS) showed a significant reduction in portal pressures in 7 cases.…”
Section: Therapymentioning
confidence: 99%
“…Initially corticosteroids were used to treat GAVE and case reports showed that 4 out of 11 patients responded to this measure [2,25,26,27,28,29,30,31, 34,36,37,38]. Typical steroid side effects, like steroid-induced diabetes mellitus and/or cushing-like illness, limit its use.…”
Section: Therapymentioning
confidence: 99%
“…Типичная локализация GAVE-синдрома -антраль-ный отдел [4]. В единичных случаях характерные проявления могут быть найдены в кардии [5], две-надцатиперстной кишке [6], прямой кишке [7].…”
Section: Introductionunclassified
“…We present the second reported case of a patient with GAVE and duodenal vascular ectasia (DUVE) associated with HSCT. GAVE is usually limited to the antrum and rarely involves either the duodenum or jejunum [1,2]. It classically appears as red spots or patches in a linear or diffuse collection endoscopically [3].…”
mentioning
confidence: 99%